Cellular Senescence and Ageing - Reed, Rebecca; Miwa, Satomi (Sub-cellular biochemistry, 2023)
Cellular senescence has become a subject of great interest within the ageing research field over the last 60 years, from the first observation in vitro by Leonard Hayflick and Paul Moorhead in 1961, to novel findings of phenotypic sub-types and senescence-like phenotype in post-mitotic cells. It has essential roles in wound healing, tumour suppression and the very first stages of human development, while causing widespread damage and dysfunction with age leading to a raft of age-related diseases. This chapter discusses these roles and their interlinking pathways, and how the observed accumulation of senescent cells with age has initiated a whole new field of ageing research, covering pathologies in the heart, liver, kidneys, muscles, brain and bone. This chapter will also examine how senescent cell accumulation presents in these different tissues, along with their roles in disease development. Finally, there is much focus on developing treatments for senescent cell accumulation in advanced age as a method of alleviating age-related disease. We will discuss here the various senolytic and senostatic treatment approaches and their successes and limitations, and the innovative new strategies being developed to address the differing effects of cellular senescence in ageing and disease.